2016
DOI: 10.1016/j.soilbio.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Species identity of biocrust-forming lichens drives the response of soil nitrogen cycle to altered precipitation frequency and nitrogen amendment

Abstract: a b s t r a c tBiological soil crusts (biocrusts) are fundamental components of drylands worldwide, and are of great importance for the regulation of ecosystem functioning. However, little is known on the role of species identify of biocrust-forming lichens in mediating the response of nitrogen (N) cycling to concurring global environmental change. Here, we conducted a microcosm study to evaluate how the species identity of biocrust-forming lichens (Diploschistes thunbergianus, Psora crystallifera and Xanthopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 64 publications
3
31
0
1
Order By: Relevance
“…The sign (positive) of the effects of mosses on microbial stability reported here might be shared across other biocrust types such as lichens, have been previously reported to promote both soil microbial activity and functioning previously (Liu et al ., ). However, it is also probable that the magnitude of the positive effects from biocrusts on soil microbial stability are dependent upon the identity of biocrusts, as recent studies point to species‐specific effects on soil functions and microbial abundance in biocrust communities (Delgado‐Baquerizo et al ., ; Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The sign (positive) of the effects of mosses on microbial stability reported here might be shared across other biocrust types such as lichens, have been previously reported to promote both soil microbial activity and functioning previously (Liu et al ., ). However, it is also probable that the magnitude of the positive effects from biocrusts on soil microbial stability are dependent upon the identity of biocrusts, as recent studies point to species‐specific effects on soil functions and microbial abundance in biocrust communities (Delgado‐Baquerizo et al ., ; Liu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, we clarify that our approach explicitly assumes that naturally occurring patches of bare ground and biocrusts are the drivers of microsite amelioration rather than reflecting pre‐existing conditions. Such an assumption is supported by previous experimental studies providing evidence that biocrusts modulate the response of soil microbes and microbially driven functions to global change drivers (Reed et al ., ; Delgado‐Baquerizo et al ., ; Liu et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Drylands are highly heterogeneous ecosystems characterized by a sparse distribution of plants, which are separated by open areas often covered by biocrusts and inhabited by soil arthropods (Delgado-Baquerizo et al, 2016a). Biocrusts are surface components typical of natural drylands, and constitute bacteria, fungi, algae, lichens and mosses that are of great importance for the regulation of N cycling processes (Delgado-Baquerizo et al, 2014;Liu et al, 2016). These biotic attributes and their interactions have unique effects on N-cycling microorganisms and ecosystem functioning in drylands (Delgado-Baquerizo et al, 2016a) due to their ability to capture and cycle water and nutrients and attract a variety of microbiota (Maestre et al, 2016).…”
Section: Key Biological Pathways Of N 2 O Emissions In Drylandsmentioning
confidence: 99%
“…Also, recent studies provide evidence that two genotypes of the same species (domesticated plants and their wild relatives) can influence ecosystem function (Delgado-Baquerizo et al, 2016a) and microbial communities (Garcia-Palacios et al, 2013;Leff et al, 2017). Species identity of plants and lichens are known to play an important role in regulating responses of soil microbial community and ecosystem functions to global climate factors, including increasing temperature, nitrogen deposition and changes in water availability, mainly through root exudation or altered microclimate (Haichar et al, 2008;Liu et al, 2016;Yuan et al, 2016). Previous studies suggested that there was intraspecies variation in plant response to climate change including elevated CO 2 and warming via altered traits such as photosynthetic capacity, leaf area and growth (Drake et al, 2015;Huang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%